PERTANGGUNGJAWABAN PIDANA AKIBAT TINDAK PIDANA PEMBAKARAN HUTAN DAN LAHAN YANG DILAKUKAN KORPORASI: ANALISIS PUTUSAN NOMOR 71/PID.B/LH/2021/PN SNT - Karjon, Sigismund Hardian; Suhartono, Slamet (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The aim of writing this article is to find out and explain the responsibility of corporations in committing criminal acts of burning forests and land as well as the judge’s considerations in imposing criminal penalties on corporations that run the palm oil business sector as stated in decision Number: 71/Pid.B/LH/2021/ PN Snt. In the criminal act of burning forests and land, the perpetrators of forest burning, both humans and legal entities (corporations), must be held accountable. Nevertheless, the majority of people still view crime as murder, rape, theft and other similar things, thus reducing the understanding that the real crime with large victims is corporate crime. The provision of criminal sanctions against corporations in the palm oil plantation industry is an effort to provide a deterrent effect so that they do not commit acts of pollution and destruction of the environment in accordance with the legal provisions in force in Indonesia. The problem in this research is how corporate responsibility is in committing criminal acts of burning forests and land and how judges consider in handing down decisions against PT. Mega Anugrah Sawit (PT.MAS). The research method used in this research is normative juridical. The results of the research show that sanctions given to perpetrators of criminal acts of burning forests and land must be strictly enforced by law. So that criminal law becomes the leading law in expressing these legal problems